Predictors of naming latencies in Lebanese Arabic using a set of 274 images - Kanj Rama; Nasser Maya; Khwaileh Tariq (Psychology of Language and Communication)
Picture-naming tasks are a widely used experimental paradigm in investigating aspects of lexical retrieval and in clinical evaluations. Psycholinguistic properties pertaining to pictorial stimuli differ across pictures and may impact the speed and accuracy of lexical retrieval. The aim of the current study was to obtain measures of naming latency and word characteristics for 274 images and their concepts. We administered a picture-naming task to 75 typical indigenous Lebanese bilingual and multilingual participants between the ages of 18 to 50 using computerized software to record latencies and responses. 42 participants from the same population participated in a rating task to gather measures of subjective frequency, familiarity, age of acquisition, and imageability. We investigated the effects of those variables on naming latency. Results showed that out of the psycholinguistic variables studied, name agreement was the only significant predictor of naming latency. The database provides clinicians and researchers with tools to cater to the specific linguistic and cultural context of multilingual Lebanese individuals.